2003
DOI: 10.1620/tjem.201.213
|View full text |Cite
|
Sign up to set email alerts
|

Partial Regeneration/Proliferation of the .BETA.-Cells in the Islets of Langerhans by Nigella sativa L. in Streptozotocin-Induced Diabetic Rats

Abstract: This experiment was carried out to investigate the effect of N. sativa L. on histopathology of pancreatic beta-cells, and blood insulin and glucose concentrations in streptozotocin-induced diabetic rats. Fifty male Wistar rats (200-250 g) were divided into two experimental groups (diabetics with no treatment and diabetics with N. sativa L. treatment), each containing twenty-five rats. Diabetes was induced in both groups by a single intraperitoneal injection of streptozotocin (STZ) (50 mg/kg). The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 8 publications
6
82
0
5
Order By: Relevance
“…However, our findings were in accordance with that of Kanter et al [34] who found that diabetic rats treated with NSO showed improvement after 10 days treatment compared to the diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
“…However, our findings were in accordance with that of Kanter et al [34] who found that diabetic rats treated with NSO showed improvement after 10 days treatment compared to the diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
“…The animals became diabetic within 24 hours after the administration of STZ. Intraperitoneal injection of 0.20 ml/kg volatile oil of N. sativa seeds for 30 days in such rats, caused gradual partial regeneration/proliferation of pancreatic beta-cells, decrease in the elevated serum glucose and increase of the lowered serum insulin concentrations [40]. Similar effects were observed in STZ induced diabetic rats with N. sativa (300 -400 mg/kg body weight) or thymoquinone (50 mg/kg body weight) once a day orally for 12 weeks [41,42].…”
Section: Antidiabetic Activity In Stz Induced Diabetic Ratsmentioning
confidence: 99%
“…STZ treated rats with blood glucose level ≥18 mmol/litre were considered to be diabetic and used in this study [15].…”
Section: For Biochemical Studymentioning
confidence: 99%